Method for measuring iodine adsorption value of wooden activated carbon
Through technical means such as crushing, grinding and infrared drying, the iodine adsorption value measurement process is optimized, which solves the problems of cumbersome operation and low efficiency in the existing technology, and achieves a more efficient and accurate iodine adsorption value determination.
Patent Information
- Application Number
- CN202411863904.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing method for determining the iodine adsorption value of wood activated carbon is complicated to operate, the sample processing time is long, the contact conditions are fixed, and the calculation is complicated, resulting in low efficiency and inaccurate results.
The uniform sample was treated by crushing and grinding, and hydrochloric acid infiltration and infrared drying techniques were used to optimize the contact conditions of the iodine standard solution with the sample, and the iodine adsorption value was calculated by titration and correction factors.
The operation process is simplified, the sample drying time is shortened, the measurement efficiency and accuracy are improved, and the measurement error and artificial error are reduced.
Smart Images

Figure CN119322148A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air purification, in particular to a method for determining the iodine adsorption value of wood activated carbon. Background Art
[0002] Wood activated carbon has been widely used in many fields such as water treatment, gas purification and chemical analysis due to its excellent adsorption performance. In particular, the iodine adsorption value is often used as an important indicator to measure its microporous structure and adsorption capacity. The traditional iodine adsorption value determination method quantitatively analyzes the adsorption capacity of activated carbon for iodine molecules through a series of steps such as crushing, heating, infiltration, oscillation, filtration and titration. However, the existing standard method has cumbersome operating steps, especially in the drying and heating process of the sample, which often takes a long time and requires high professional skills of the operator. At the same time, the table lookup calculation also increases the complexity of the experiment.
[0003] The prior art has some shortcomings in the determination of iodine adsorption value of wood activated carbon. First, the sample processing is not simplified enough, especially the steps of sample crushing and drying are time-consuming, which affects the experimental efficiency. Secondly, the contact time and conditions between the sample and the iodine solution are relatively fixed, which limits the flexibility of the experiment. Especially when calculating the correction factor, the traditional method needs to be completed by looking up the table, which not only increases the complexity of the experimental process, but also easily introduces human errors. Therefore, there is an urgent need for an improved method that simplifies the operating steps, improves the measurement efficiency and ensures the measurement accuracy. Summary of the invention
[0004] In view of the above existing problems, the present invention is proposed.
[0005] Therefore, the present invention provides a method for determining the iodine adsorption value of wood activated carbon to solve the problems of cumbersome operation, insufficient contact and complex calculation in the existing method for determining the iodine adsorption value of wood activated carbon, resulting in low efficiency and inaccurate results of iodine adsorption value determination.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for determining the iodine adsorption value of wood activated carbon, which comprises: The wood activated carbon sample is crushed and ground to obtain a uniform and fine sample; Weigh a certain amount of uniform and fine sample and completely infiltrate it with hydrochloric acid; The infrared drying technology is used to dry the wetted samples, and the dried samples are cooled to room temperature; Add the calibrated iodine standard solution to the sample cooled to room temperature, so that the iodine standard solution is in full contact with the sample; Separating the fully contacted iodine standard solution from the sample to obtain a filtrate containing residual iodine; A fixed volume of sample is taken from the filtrate containing residual iodine and titrated with a calibrated sodium thiosulfate standard solution. The volume of sodium thiosulfate solution consumed after the titration is completed; Based on the titration results, combined with specific correction factors, the iodine adsorption value is calculated.
[0007] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, the wood activated carbon sample is crushed and ground to obtain a uniform and fine sample, which comprises the following steps: Take a dry wood activated carbon raw material without large block impurities from a conventional wood activated carbon raw material as a sample; The taken out wood activated carbon sample was placed in a high-efficiency laboratory pulverizer for preliminary pulverization; The coarse wood activated carbon sample after preliminary crushing is transferred to a ball mill for fine grinding to obtain a uniform fine powder state sample; After the ball mill is finished grinding, the sample is placed in an air-isolated container and tested with a laser particle size analyzer to determine whether it meets the uniformity of particle size distribution; The wood activated carbon samples that have passed the particle size test are screened for the second time to screen out the fine powder wood activated carbon samples with qualified particle size; After screening, the fine powder wood activated carbon samples with qualified particle size are sealed in a desiccator for storage.
[0008] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, a certain amount of uniform and fine sample is weighed and completely infiltrated with hydrochloric acid, which includes the following steps: A certain amount of ground wood activated carbon sample was taken out from the dryer by stepwise addition and placed on an electronic analytical balance to weigh the mass. Activated carbon samples; After weighing, quickly transfer the wood activated carbon sample to the prepared clean, dry conical flask and seal it immediately; Use a pipette to accurately measure a hydrochloric acid solution of fixed concentration and volume, and gradually add the hydrochloric acid solution into a conical flask containing the weighed wood activated carbon sample; After adding the hydrochloric acid solution, gently shake the conical flask in a clockwise direction to fully mix the hydrochloric acid solution with the wood activated carbon sample to complete the hydrochloric acid complete infiltration operation.
[0009] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, the method comprises the following steps: using infrared drying technology to dry the soaked sample, and cooling the dried sample to room temperature. After the hydrochloric acid impregnation operation is completed, the impregnated wood activated carbon sample is immediately transferred from the conical flask to the special sample dish of the infrared drying equipment; Use short-wave infrared drying technology to quickly migrate and evaporate the moisture in the sample from the inside to the outside through infrared radiation to obtain a dried sample; The dried sample was taken out from the special sample dish and cooled to room temperature in a desiccator in a closed environment.
[0010] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, the method comprises the following steps: adding a calibrated iodine standard solution to a sample cooled to room temperature, so that the iodine standard solution is fully in contact with the sample, Take out the wood activated carbon sample that has been dried and cooled to room temperature and put it into a conical flask; Use a precision pipette to measure the calibrated volume. The concentration is Add the iodine standard solution into the conical flask containing the wood activated carbon sample; After adding, seal the conical flask immediately and shake the flask to allow the iodine solution to fully contact with the wood activated carbon particles; After shaking, let the conical flask stand still and observe whether the activated carbon sample in the conical flask fully reacts with the iodine molecules in the iodine solution and reaches adsorption equilibrium.
[0011] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, the method comprises the following steps: separating the fully contacted iodine standard solution from the sample to obtain a filtrate containing residual iodine: Place a glass funnel on a clean filtrate collection container, put a medium-speed qualitative filter paper into the funnel and wet the filter paper with a small amount of deionized water to make the filter paper fit completely with the funnel wall; The mixture of iodine solution and activated carbon sample that have reached adsorption equilibrium is poured into the funnel at a constant speed through a glass rod for filtration; During the filtration process, observe the flow rate of the liquid through the filter paper and the clarity of the filtrate. If the flow rate is uneven and the filtrate becomes turbid, replace the filter paper and filter again. After filtration is completed, collect the filtrate containing residual iodine into a clean conical flask for storage.
[0012] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, a fixed volume of sample is taken from the filtrate containing residual iodine, titrated with a calibrated sodium thiosulfate standard solution, and after the titration, the consumed volume of the sodium thiosulfate solution is recorded, which includes the following steps: Use a stirring rod to stir the filtrate containing residual iodine in the conical flask evenly; Insert the pipette into the middle layer of the stirred filtrate and take out The liquid is used as the sample; Transfer the sampled filtrate to a clean titration bottle and store it in a light-shielded environment; Add a certain mass fraction of starch indicator solution to the titration bottle containing the filtrate sample to make the filtrate appear dark blue; Use the calibrated concentration of As a titrant, add a standard solution of sodium thiosulfate dropwise into the titration bottle containing the filtrate and starch indicator; When the color of the solution gradually changes from dark blue to light blue and finally fades to colorless, it indicates that the iodine in the solution has been completely reduced. The titration is over and the consumed volume of sodium thiosulfate solution is recorded. .
[0013] As a preferred embodiment of the method for determining the iodine adsorption value of wood activated carbon of the present invention, the iodine adsorption value is calculated based on the titration result in combination with a specific correction factor, and the expression is: ; in, Indicates the iodine adsorption value of the sample. represents the concentration of the iodine standard solution, Indicates the concentration of sodium thiosulfate standard solution, Indicates the volume of sodium thiosulfate standard solution consumed, Indicates the volume of sodium thiosulfate standard solution consumed, Indicates the volume of the filtrate taken. Indicates the sample mass, represents the molar mass of iodine, Indicates a specific correction factor.
[0014] In a second aspect, the present invention provides a computer device comprising a memory and a processor, wherein the memory stores a computer program, wherein: when the computer program is executed by the processor, any step of the method for determining the iodine adsorption value of wood activated carbon as described in the first aspect of the present invention is implemented.
[0015] In a third aspect, the present invention provides a computer-readable storage medium having a computer program stored thereon, wherein: when the computer program is executed by a processor, any step of the method for determining the iodine adsorption value of wood activated carbon as described in the first aspect of the present invention is implemented.
[0016] The beneficial effects of the present invention are as follows: by crushing and grinding the wood activated carbon sample, the uniformity of the sample is ensured, the surface area of the sample is made consistent, and the measurement error caused by uneven particle size is reduced; at the same time, after the hydrochloric acid infiltration treatment, it is no longer necessary to heat to a slight boil and cool, but the infrared drying technology is directly used, which not only greatly shortens the sample drying time, but also effectively maintains the microporous structure of the activated carbon, and avoids the damage of high temperature to the adsorption performance; by optimizing the contact conditions between the sample and the iodine standard solution, sufficient reaction is ensured, and the adsorption efficiency of iodine molecules is further improved; a fixed correction factor is introduced to replace the traditional table lookup calculation, simplify the calculation process, and reduce the experimental complexity and error sources. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0018] Figure 1 This is a flow chart of the method for determining the iodine adsorption value of wood activated carbon in Example 1.
[0019] Figure 2 This is a schematic diagram of the hydrochloric acid infiltration operation in Example 1. DETAILED DESCRIPTION
[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0022] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0023] Example 1, reference Figure 1 and Figure 2 , which is the first embodiment of the present invention, provides a method for determining the iodine adsorption value of wood activated carbon, comprising the following steps: S1. Crush and grind the wood activated carbon sample to obtain a uniform and fine sample.
[0024] S1.1. Take dry wood activated carbon raw materials without large block impurities from conventional wood activated carbon raw materials as samples; place the taken wood activated carbon samples in a high-efficiency laboratory grinder for preliminary crushing; transfer the coarse-grained wood activated carbon samples after preliminary crushing to a ball mill for fine grinding to obtain a sample in a uniform fine powder state; after the ball mill grinding is completed, place the sample in an air-isolated container, and use a laser particle size analyzer to test the ground sample to determine whether it meets the uniformity of particle size distribution; perform secondary screening on the wood activated carbon samples that pass the particle size test to screen out the fine powder wood activated carbon samples with qualified particle size; after the screening is completed, the fine powder wood activated carbon samples with qualified particle size are sealed in a desiccator for storage.
[0025] Specifically, the formula for determining the particle size distribution uniformity index is: ; in, represents the standard deviation of the particle size distribution, Indicates The particle size, represents the average particle size of the sample, Indicates the number of sample particles, Indicates the sample particle index.
[0026] S2. Weigh a certain amount of uniform and fine sample and completely infiltrate it with hydrochloric acid.
[0027] S2.1. Take a certain amount of ground wood activated carbon sample from the dryer by stepwise addition and weigh it on an electronic analytical balance. Activated carbon samples.
[0028] Among them, the accuracy error of the electronic analytical balance is within ±0.0001g.
[0029] S2.2. Transfer the weighed wood activated carbon sample quickly to a clean, dry conical flask and seal it immediately. Use a pipette to accurately measure the hydrochloric acid solution of fixed concentration and volume, and gradually add the hydrochloric acid solution to the conical flask containing the weighed wood activated carbon sample.
[0030] Specifically, the hydrochloric acid solution is 10mL with a concentration of 5wt% and a mass fraction of 5%, that is, the solution contains 5g of hydrochloric acid and 95g of water; before the experiment, the pipette needs to be calibrated to ensure that the volume error measured does not exceed ±0.01mL.
[0031] S2.3. After adding the hydrochloric acid solution, gently shake the conical flask in a clockwise direction to fully mix the hydrochloric acid solution with the wood activated carbon sample to complete the hydrochloric acid complete infiltration operation.
[0032] Specifically, the shaking time is set to 1-2 minutes to ensure that the hydrochloric acid can evenly infiltrate the internal pores of the activated carbon particles. Insufficient time may lead to incomplete infiltration, while too long time may lead to excessive dissolution of the sample particles or structural damage. During the shaking process, observe the contact between the activated carbon in the conical flask and the hydrochloric acid solution. Ensure that the hydrochloric acid solution can completely cover the activated carbon particles and no obvious bubbles remain on the surface of the particles. After shaking, let the conical flask stand for 5 minutes to allow the hydrochloric acid solution to further react with the activated carbon to ensure complete infiltration.
[0033] S3. Use infrared drying technology to dry the soaked sample and cool the dried sample to room temperature.
[0034] S3.1. After the hydrochloric acid impregnation operation is completed, immediately transfer the impregnated wood activated carbon sample from the conical flask to the special sample dish of the infrared drying equipment.
[0035] The sample dish should be made of stainless steel or heat-resistant glass and should be cleaned with deionized water and then dried.
[0036] S3.2. Use short-wave infrared drying technology to quickly migrate and evaporate the moisture in the sample from the inside to the outside through infrared radiation to obtain a dried sample.
[0037] The principle of infrared drying is that the energy of infrared radiation resonates with the water molecules on the surface of the sample, causing the water molecules to vibrate rapidly and evaporate. Infrared radiation can quickly transfer the moisture inside the sample to the surface, thereby accelerating the overall drying process.
[0038] S3.3. Take out the dried sample from the special sample dish and cool it to room temperature in a dryer in a closed environment.
[0039] In this embodiment, a vacuum dryer or a sealed dryer is used for cooling to prevent the sample from being exposed to the air and absorbing moisture. A low humidity environment should be maintained in the dryer, and the humidity should be controlled at 20-30% RH. If a vacuum dryer is used, the air in the dryer is discharged through the exhaust system to cool the sample in a low-pressure environment to further prevent moisture back-absorption.
[0040] S4. Add the calibrated iodine standard solution to the sample cooled to room temperature, so that the iodine standard solution is in full contact with the sample.
[0041] S4.1. Take out the wood activated carbon sample that has been dried and cooled to room temperature and put it into a conical flask; use a precision pipette to measure the calibrated volume. The concentration is Add the iodine standard solution into the conical flask containing the wood activated carbon sample.
[0042] Specifically, the concentration and volume of the iodine standard solution should be determined according to the experimental requirements.
[0043] S4.2. Seal the conical flask immediately after adding and shake the flask to allow the iodine solution to fully contact with the wood activated carbon particles. After shaking, let the conical flask stand and observe whether the activated carbon sample in the conical flask fully reacts with the iodine molecules in the iodine solution and reaches adsorption equilibrium.
[0044] Specifically, the adsorption equilibrium principle is that iodine molecules gradually occupy the adsorption sites on the activated carbon surface until a state of equilibrium is reached.
[0045] S5. Separate the fully contacted iodine standard solution from the sample to obtain a filtrate containing residual iodine.
[0046] S5.1. Place a glass funnel on a clean filtrate collection container, put a medium-speed qualitative filter paper into the funnel and moisten the filter paper with a small amount of deionized water so that the filter paper fits completely against the funnel wall.
[0047] Specifically, the pore size of medium-speed qualitative filter paper is 8-12µm, which is suitable for separating finer particles of solid matter.
[0048] S5.2. Pour the mixture of iodine solution and activated carbon sample that have reached adsorption equilibrium into the funnel at a constant speed through a glass rod for filtration. During the filtration process, observe the flow rate of the liquid through the filter paper and the clarity of the filtrate. When the flow rate is uneven and turbidity appears in the filtrate, replace the filter paper and filter again. After the filtration is completed, collect the filtrate containing residual iodine in a clean conical flask for storage.
[0049] Specifically, constant speed control is recommended to pour 10-15 mL of the mixture every 10-15 seconds to ensure that the solution pressure remains stable during the filtration process to avoid filter paper rupture.
[0050] The filtration principle is that during the filtration process, the liquid and solid are effectively separated by the capillary action of the filter paper. The iodine molecules dissolved in the iodine solution will pass through the filter paper, while the wood activated carbon particles will be retained by the filter paper.
[0051] S6. Take out a fixed volume of sample from the filtrate containing residual iodine, titrate it with a calibrated sodium thiosulfate standard solution, and record the consumed volume of the sodium thiosulfate solution after the titration.
[0052] S6.1. Use a stirring rod to stir the filtrate containing residual iodine in the conical flask evenly; insert a pipette into the middle layer of the stirred filtrate and take out a volume of of liquid as a sample.
[0053] Specifically, the sampling position is selected in the middle layer of the filtrate to avoid absorbing impurities on the liquid surface or particles deposited at the bottom.
[0054] S6.2. Transfer the filtrate sample to a clean titration bottle and store it in a light-shielded environment; add a certain mass fraction of starch indicator solution to the titration bottle containing the filtrate sample to make the filtrate appear dark blue.
[0055] Specifically, the starch indicator can react with iodine to turn iodine into blue in the solution. Adding the starch indicator makes the color change of iodine more obvious during the titration process, making it easier to determine the titration endpoint, thereby ensuring the accuracy of the titration result.
[0056] S6.3, use the calibrated concentration The sodium thiosulfate standard solution is used as the titrant and added dropwise into the titration bottle containing the filtrate and starch indicator; when the color of the solution gradually changes from dark blue to light blue and finally fades to colorless, it indicates that the iodine in the solution has been completely reduced, the titration is completed and the consumed volume of the sodium thiosulfate solution is recorded. .
[0057] Specifically, by titrating gradually and accurately determining the endpoint, it is ensured that the consumption of the sodium thiosulfate solution can accurately reflect the amount of residual iodine in the filtrate, thereby avoiding the error caused by excessive titration. Compared with the rapid titration in the traditional scheme, this scheme emphasizes the control of the titration speed, especially the slow addition when approaching the endpoint, to ensure the accurate determination of the endpoint and reduce the possibility of excessive titration.
[0058] S7. Based on the titration results and the specific correction factor, the iodine adsorption value is calculated as follows: ; in, Indicates the iodine adsorption value of the sample. represents the concentration of the iodine standard solution, Indicates the concentration of sodium thiosulfate standard solution, Indicates the volume of sodium thiosulfate standard solution consumed, Indicates the volume of sodium thiosulfate standard solution consumed, Indicates the volume of the filtrate taken. Indicates the sample mass, represents the molar mass of iodine, Indicates a specific correction factor.
[0059] It should be noted that by using a correction factor of 0.9, the systematic error in the experimental process was corrected to ensure the accuracy and repeatability of the results.
[0060] This embodiment also provides a computer device, which is suitable for the method for determining the iodine adsorption value of wood activated carbon, including: a memory and a processor; the memory is used to store computer executable instructions, and the processor is used to execute computer executable instructions to implement the method for determining the iodine adsorption value of wood activated carbon proposed in the above embodiment.
[0061] The computer device may be a terminal, and the computer device includes a processor, a memory, a communication interface, a display screen and an input device connected through a system bus. Among them, the processor of the computer device is used to provide computing and control capabilities. The memory of the computer device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system and a computer program. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The communication interface of the computer device is used to communicate with an external terminal in a wired or wireless manner, and the wireless manner can be achieved through WIFI, an operator network, NFC (near field communication) or other technologies. The display screen of the computer device may be a liquid crystal display screen or an electronic ink display screen, and the input device of the computer device may be a touch layer covered on the display screen, or a key, trackball or touchpad provided on the housing of the computer device, or an external keyboard, touchpad or mouse, etc.
[0062] This embodiment also provides a storage medium on which a computer program is stored. When the program is executed by a processor, the method for determining the iodine adsorption value of wood activated carbon proposed in the above embodiment is implemented; the storage medium can be implemented by any type of volatile or non-volatile storage device or a combination thereof, such as static random access memory (Static Random Access Memory, referred to as SRAM), electrically erasable programmable read-only memory (Electrically Erasable Programmable Read-Only Memory, referred to as EEPROM), erasable programmable read-only memory (Erasable Programmable Read-Only Memory, referred to as EPROM), programmable read-only memory (Programmable Red-Only Memory, referred to as PROM), read-only memory (Read-Only Memory, referred to as ROM), magnetic storage, flash memory, magnetic disk or optical disk.
[0063] In summary, the present invention ensures the uniformity of the sample by crushing and grinding the wood activated carbon sample, makes the surface area of the sample consistent, and reduces the measurement error caused by uneven particle size; at the same time, after the hydrochloric acid infiltration treatment, it is no longer necessary to heat to a slight boil and cool, but directly adopts infrared drying technology, which not only greatly shortens the sample drying time, but also effectively maintains the microporous structure of the activated carbon, and avoids the damage of high temperature to the adsorption performance; by optimizing the contact conditions between the sample and the iodine standard solution, sufficient reaction is ensured, and the adsorption efficiency of iodine molecules is further improved; a fixed correction factor is introduced to replace the traditional table lookup calculation, simplify the calculation process, and reduce the experimental complexity and error sources.
[0064] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for determining the iodine adsorption value of wood activated carbon, characterized in that: include, The wood activated carbon sample is crushed and ground to obtain a uniform and fine sample; Weigh a certain amount of uniform and fine sample and completely infiltrate it with hydrochloric acid; The infrared drying technology is used to dry the wetted samples, and the dried samples are cooled to room temperature; Add the calibrated iodine standard solution to the sample cooled to room temperature, so that the iodine standard solution is in full contact with the sample; Separating the fully contacted iodine standard solution from the sample to obtain a filtrate containing residual iodine; Take a fixed volume of sample from the filtrate containing residual iodine and titrate it with a calibrated sodium thiosulfate standard solution. After the titration, record the consumed volume of the sodium thiosulfate solution. Based on the titration results, combined with specific correction factors, the iodine adsorption value is calculated.
2. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 1, characterized in that: The steps of crushing and grinding the wood activated carbon sample to obtain a uniform and fine sample include: Take a dry wood activated carbon raw material without large block impurities from a conventional wood activated carbon raw material as a sample; The taken out wood activated carbon sample was placed in a high-efficiency laboratory pulverizer for preliminary pulverization; The coarse wood activated carbon sample after preliminary crushing is transferred to a ball mill for fine grinding to obtain a uniform fine powder state sample; After the ball mill is finished grinding, the sample is placed in an air-isolated container and tested with a laser particle size analyzer to determine whether it meets the uniformity of particle size distribution; The wood activated carbon samples that have passed the particle size test are screened for the second time to screen out the fine powder wood activated carbon samples with qualified particle size; After screening, the fine powder wood activated carbon samples with qualified particle size are sealed in a desiccator for storage.
3. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 2, characterized in that: Weigh a certain amount of uniform and fine sample and use hydrochloric acid to completely infiltrate it, including the following steps: A certain amount of ground wood activated carbon sample was taken out from the dryer by stepwise addition and placed on an electronic analytical balance to weigh the mass. Activated carbon samples; Transfer the weighed wood activated carbon sample into a clean and dry conical flask and seal it; Use a pipette to accurately measure a hydrochloric acid solution of fixed concentration and volume, and gradually add the hydrochloric acid solution into a conical flask containing the weighed wood activated carbon sample; After adding the hydrochloric acid solution, gently shake the conical flask in a clockwise direction to fully mix the hydrochloric acid solution with the wood activated carbon sample to complete the hydrochloric acid complete infiltration operation.
4. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 3, characterized in that: Using infrared drying technology to dry the infiltrated sample and cooling the dried sample to room temperature includes the following steps: After the hydrochloric acid impregnation operation is completed, the impregnated wood activated carbon sample is transferred from the conical flask to a special sample dish of the infrared drying equipment; Use short-wave infrared drying technology to migrate and evaporate the moisture in the sample from the inside to the outside through infrared radiation to obtain a dried sample; The dried sample was taken out from the special sample dish and cooled to room temperature in a desiccator in a closed environment.
5. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 4, characterized in that: Adding a calibrated iodine standard solution to a sample cooled to room temperature so that the iodine standard solution is fully in contact with the sample comprises the following steps: Take out the wood activated carbon sample that has been dried and cooled to room temperature and put it into a conical flask; Use a precision pipette to measure the calibrated volume. The concentration is Add the iodine standard solution into the conical flask containing the wood activated carbon sample; After adding, seal the conical flask and shake the flask to allow the iodine solution to fully contact with the wood activated carbon particles; After shaking, let the conical flask stand still and observe whether the activated carbon sample in the conical flask fully reacts with the iodine molecules in the iodine solution and reaches adsorption equilibrium.
6. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 5, characterized in that: The method of separating the fully contacted iodine standard solution from the sample to obtain a filtrate containing residual iodine comprises the following steps: Place a glass funnel on a clean filtrate collection container, put a medium-speed qualitative filter paper into the funnel and wet the filter paper with a small amount of deionized water; The mixture of iodine solution and activated carbon sample that have reached adsorption equilibrium is poured into the funnel at a constant speed through a glass rod for filtration; During the filtration process, observe the flow rate of the liquid through the filter paper and the clarity of the filtrate. If the flow rate is uneven and the filtrate becomes turbid, replace the filter paper and filter again. After filtration is completed, collect the filtrate containing residual iodine into a clean conical flask for storage.
7. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 6, characterized in that: A fixed volume of sample is taken from the filtrate containing residual iodine, and titrated with a calibrated sodium thiosulfate standard solution. After the titration, the consumed volume of the sodium thiosulfate solution is recorded, which includes the following steps: Use a stirring rod to stir the filtrate containing residual iodine in the conical flask evenly; Insert the pipette into the middle layer of the stirred filtrate and take out The liquid is used as the sample; Transfer the sampled filtrate to a clean titration bottle and store it in a light-shielded environment; Add a certain mass fraction of starch indicator solution to the titration bottle containing the filtrate sample to make the filtrate appear dark blue; Use the calibrated concentration of As a titrant, add a standard solution of sodium thiosulfate dropwise into the titration bottle containing the filtrate and starch indicator; When the color of the solution gradually changes from dark blue to light blue and finally fades to colorless, it indicates that the iodine in the solution has been completely reduced. The titration is over and the consumed volume of sodium thiosulfate solution is recorded. .
8. The method for determining the iodine adsorption value of wood activated carbon as claimed in claim 7, characterized in that: Based on the titration results, combined with a specific correction factor, the iodine adsorption value is calculated as follows: ; in, Indicates the iodine adsorption value of the sample. represents the concentration of the iodine standard solution, Indicates the concentration of sodium thiosulfate standard solution, Indicates the volume of sodium thiosulfate standard solution consumed, Indicates the volume of sodium thiosulfate standard solution consumed, Indicates the volume of the filtrate taken. Indicates the sample mass, represents the molar mass of iodine, Indicates a specific correction factor.
Citation Information
Patent Citations
Device and method for automatically detecting iodine adsorption value of activated carbon
CN118090652A
Air purification antibacterial activated carbon and preparation method thereof
CN118384855A
Rapid determination method for iodine adsorption value of activated carbon
CN118655267A
Infrared drying equipment for activated carbon
CN219347198U
Aerial Work Assemblies for Aerial Work Vehicles
KR1020240173130A